Systematization and justification of recreational mechanisms of laughter in the system of personality - IVANOVA, Olena (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
B a c k g r o u n d . A theoretical and methodological analysis of approaches to recreational laughter mechanisms is presented. Laughter is regarded as an individual psycho-physiological reaction to a certain unexpected situation that is formed based on emotionally colored personal senses and value ideas, shown in various expressions of joy. M e t h o d s . Given the multilevel phenomenon, the mechanisms of its influence on the individual are analyzed in the context of philosophical, theological, cultural, pedagogical, psychophysiological, and psychological (social) approaches. Theoretical research methods were used: analysis of scientific sources on the research topic, system analysis, synthesis, generalization of scientific approaches, classification and specification of laughter mechanisms in the personality system. R e s u l t s . In the context of the restorative mechanisms of laughter, its connection with direct play and joy arising in the process and accompanied by release, relief, satisfaction, and relaxation, helping to go beyond the ordinary, is considered. It has been revealed that laughter is also one of the ways for the soul to realize and liberate itself through release from fears and mental tension. It has also been proven that laughter serves as a certain stimulator of brain activity, activates imagination and fantasy, that is, promotes creativity. It is substantiated that laughter is a necessary element of stress relief, has a restorative and regenerative effect on the physical and psycho-emotional state, acts on the physiological and hormonal levels, activates the frontal, motor lobes, brain stem and cortex, hippocampus, thalamus and limbic system. It is argued that during laughter a spastic effect is realized, it affects the regulation of breathing, unites the physical and mental principle. C o n c l u s i o n s . It was determined that laughter, as an important personal resource of interaction with other people, plays a special role in the prevention and correction of unwanted stress states of the individual. It has been found that it greatly helps a person to adapt to various unexpected situations, because laughter unites people, helps to free oneself from the influence of fears, anxieties and doubts and allows to manifest the true qualities laid down from birth, such as love, clarity of perception, compassion, joy, enthusiasm, gratitude and wisdom. Laughter can help you make good decisions and show kindness in your actions.